Thermomechanically controlled fluorescence anisotropy in thin films of InP/ZnS quantum dots. Issue 18 (17th August 2021) - Parzyszek, Sylwia; Pociecha, Damian; Wolska, Joanna Maria; Lewandowski, Wiktor
Abstract : A thin-film, macroscopic scale source of partially polarized light is achieved via self-assembly of isotropic InP/ZnS quantum dots. Such materials will play a fundamental role in designing cost-effective light-emitting devices. Abstract : Macroscopic scale sources of polarized light play a fundamental role in designing light-emitting devices. In this communication we report the formation of nano- and macro-scale ordered, layered assemblies of InP/ZnS quantum dots (QDs) exhibiting fluorescence anisotropy (FA), as well as thermo- and mechano-responsive properties. The long-range organization of small, quasi-isotropic nanoparticles was achieved by introducing liquid crystal molecules to the surface of QDs, without the need to use an organic matrix. Melting/crystallization of the ligand at 95 deg. C translated to a reversible reconfiguration of QDs thin film between 2D layered and body-centered cubic structures, characteristic for a temperature range below and above the melting point, respectively. The low-temperature, layered structure exhibited mechano-responsiveness which was key to introduce and control the sample alignment. Interestingly, transverse and parallel alignment modes of QDs layers were achieved, depending on the temperature of mechanical shearing. As prepared QD samples exhibited fluorescence anisotropy strongly correlated to the macroscopic orientation of the layers. Correlated small-angle X-ray diffraction (SAXRD) and fluorescence spectroscopy studies confirmed the mm-scale alignment of the thin films of QDs. Such films may be advantageous for developing efficient, densely packed, and uniform macro-scale FA sources.